The effect of green tea consumption on oxidative stress markers and cognitive function in patients with Alzheimer's disease: A prospective intervention study - Hourolein Arab; Soleiman Mahjoub; Karimollah Hajian-Tilaki; Mehdi Moghadasi (Babol University of Medical Sciences, 2016)
Background: Alzheimer’s disease (AD) is the most prevalent degenerative disorder of the brain among elderly individuals. Many studies indicate that oxidative stress is an important pathogenic factor which involves oxidizing macromolecules such as DNA, lipids, and proteins in AD. Green tea is a rich source of antioxidant compounds that can remove radical oxygen species. The purpose of this study was to investigate the influence of green tea consumption on markers of oxidative stress in AD. Methods: In this prospective intervention study, 30 patients with severe AD were recruited. The diagnosis of AD was made based on the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer’s disease and Related Disorders Association (NINCDS/ADRDA) criteria. Brain magnetic resonance imaging (MRI) and computed tomography (CT) scan as well as Mini-Mental State Examination (MMSE) were performed for all participants in which four green tea pills were administered daily for 2 months (2 g/day in 2 divided doses). The plasma total antioxidant capacity, 8-hydroxy-2’-deoxyguanosine levels (8-OHdG), malondialdehyde (MDA), carbonyl content, and MMSE scores were measured at baseline and at the end of the study period. Results: The levels of MDA, 8-OHdG and carbonyl decreased significantly as compared to baseline values (P=0.002, P=0.001 and P=0.037, respectively). Whereas, the total antioxidant capacity of plasma and MMSE scores significantly increased at end point (P=0.000, P=0.043, respectively). Conclusion: The findings indicate that consumption of green tea for two months by with the improvement of antioxidant system exerts beneficial effect on cognitive function.